경흔적 수에 의한 수삼의 연근판별 - 이성식(Sung-Sik Lee); 이장호(Jang-Ho Lee); 안인옥(In-Ok Ahn); 김영창(Young-Chang Kim); 방경환(Kyong-Hwan Bang); 현동윤(Dong-Yun Hyun) (Journal of ginseng research, 2007)
This experiment was conducted to find identification of ginseng root's age using the number of stem vestiges in rhizome. The number of stem vestiges in rhizome is a useful key to confirm the age of ginseng root as follow : 4-year-old root has two, 5-year-old root has three, 6-year-old root has four. The distribution of stem vestiges in rhizome each year root are as follow : 2 stem vestiges in 4-year-old root is 89.5%, 3 stem vestiges in 5-year-old root is 79.7%, 4 stem vestiges in 6-year-old root is 46.3%. However, the limiting factors of identification of ginseng root's age using the number of stem vestiges in rhizome is appearance of multi-stem per plant and appearance of destroyed stem vestige in rhizome. The ratio of appearance of multi-stem per plant and destroyed stem vestige in rhizome are increased according to root age. 본 시험은 경흔적수 측정법으로 수삼의 연근을 판별하기 위하여, 4, 5, 6년근의 경흔적수 발생실태를 조사하였다. 경흔적수를 이용한 연근판별법은 3년근 경흔적부터 식별가능하여 경흔적수에 2를 더하면 년근판별이 가능하였다. 년근별 경흔적수가 4년생에서 2개 발생율이 89.5%, 5년생에서 3개 발생율이 79.7% 6년생에서 4개 발생율이 46.3%로, 4, 5년근의 판별은 가능하였으나, 6년근 판별은 정확도가 낮아 보조자료로 활용함이 타당하였다. 경흔적을 이용한 연근 판별의 제한요인으로 뇌두파손과 다경발생임을 확인하였고, 뇌두파손율과 다경발생율은 년근이 증가함에 따라 증가되었다.